2016
DOI: 10.1007/jhep08(2016)041
|View full text |Cite
|
Sign up to set email alerts
|

Universal bounds on charged states in 2d CFT and 3d gravity

Abstract: Abstract:We derive an explicit bound on the dimension of the lightest charged state in two dimensional conformal field theories with a global abelian symmetry. We find that the bound scales with c and provide examples that parametrically saturate this bound. We also prove that any such theory must contain a state with charge-to-mass ratio above a minimal lower bound. We comment on the implications for charged states in three dimensional theories of gravity.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
108
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(114 citation statements)
references
References 52 publications
2
108
0
Order By: Relevance
“…A similar bound in the presence of a U(1) global symmetry has been found in [27]. In [14], it was also observed that the level-one g = A 1 , A 2 , G 2 , D 4 , E 8 Wess-Zumino-Witten (WZW) models can be realized on the upper limit of the dimension gap of scalar primaries at the corresponding values of central charge.…”
Section: Jhep12(2017)045supporting
confidence: 66%
“…A similar bound in the presence of a U(1) global symmetry has been found in [27]. In [14], it was also observed that the level-one g = A 1 , A 2 , G 2 , D 4 , E 8 Wess-Zumino-Witten (WZW) models can be realized on the upper limit of the dimension gap of scalar primaries at the corresponding values of central charge.…”
Section: Jhep12(2017)045supporting
confidence: 66%
“…We regard this as a version of the WGC in three dimensions. The recent work [30] also uses modular invariance to place an upper bound on the conformal dimension of charged operators, in a more general setting than the one we consider (the results of [30] are also valid for a noncompact gauge group, whereas ours rely on compactness in an essential way).…”
Section: Jhep10(2016)159mentioning
confidence: 99%
“…This will allow us to define a black hole threshold (see e.g. [30]) for operators corresponding to charged BTZ black holes in subsection 4.2, which is the CFT version of an extremality bound.…”
Section: Jhep10(2016)159mentioning
confidence: 99%
“…The blocks are also the basic components of the conformal bootstrap program [16][17][18][19][20]. Knowing their explicit forms would greatly assist the study of 2d CFTs and 3d gravity using the bootstrap [5,[21][22][23][24][25][26].…”
Section: Jhep03(2017)167mentioning
confidence: 99%